Plasma initiation and preliminary magnetic control in the HL-2M tokamak. (28th June 2021) - Song, X.; Song, X.M.; Li, B.; Zhou, J.; Nardon, E.; Heumann, H.; Faugeras, B.; Li, J.X.; Wang, Sh.; Liang, Sh.Y.; Zhang, J.Z.; Sun, T.F.; et al.
Abstract: The first plasmas have been achieved in the HL-2M tokamak by fulfilling the usual criteria for plasma breakdown, i.e. optimal working gas pressure, field null configuration of poloidal magnetic field, reasonable toroidal electrical field and clean wall conditions. The characterization of plasma initiation, such as identification of initiation time and position, is performed by diagnostic data analysis and numerical simulation. A model-based method, which enables dedicated pick-up sensors to estimate plasma radial position in real time, is applied for the limiter plasma shape in the first plasma commissioning phase. For a circular cross-section plasma, feedback control on plasma current and radial position allowed us to extend discharge durations to ∼250 ms associated with a 120 kA plasma current in flat-top. Preliminary plasma equilibrium reconstruction by the NICE code from pick-up sensors and flux loops, as well as interferometry measurements, gives plasma boundaries, plasma profiles of toroidal current density and safety factor, as well as electron density, in an offline way.